STRATEGI MANAJEMEN KEPALA SEKOLAH DASAR UNTUK MENYUKSESKAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) - Suharyati, Suharyati; Hari Mukti, Wiji Aziiz; Asvio, Nova; Vivekanantharasa, Raveenthiran; Utama, Esen Pramudya (UIN Imam Bonjol Padang, 2024)
School principals are accountable for ensuring the success of the Pancasila Student Profile Strengthening Project, a program that strives to develop students’ comprehension, appreciation, and application of Pancasila ideals. This essay aims to provide elementary school administrators with a management plan that will enable them to successfully implement the project of raising the profile of Pancasila students. Research in libraries is the method employed. The research results show that the Project for Strengthening the Pancasila Student Profile is one part of the independent curriculum with noble goals that require management strategies from the school principal to implement it to succeed. Management strategies that a school principal can implement to make the project of strengthening the profile of Pancasila students a success: 1) Formation of a Work Team; 2) Training and Development; 3) Parental and Community Involvement; and 4) Continuous Monitoring and Evaluation.